2004
DOI: 10.1016/s1097-2765(04)00127-3
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus U8 snoRNA Binding Protein Is a Conserved Nuclear Decapping Enzyme

Abstract: U8 snoRNP is required for accumulation of mature 5.8S and 28S rRNA in vertebrates. We are identifying proteins that bind U8 RNA with high specificity to understand how U8 functions in ribosome biogenesis. Here, we characterize a Xenopus 29 kDa protein (X29), which we previously showed binds U8 RNA with high affinity. X29 and putative homologs in other vertebrates contain a NUDIX domain found in MutT and other nucleotide diphosphatases. Recombinant X29 protein has diphosphatase activity that removes m(7)G and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 47 publications
5
94
0
Order By: Relevance
“…Consistent with a previous report, Nudt16 hydrolyzed the GpppRNA unmethylated capped RNA and generated GMP decapping product ( Fig. 1C; Ghosh et al 2004). Unexpectedly, Dcp2 could also hydrolyze GpppRNA and released GDP.…”
Section: Identification Of Mammalian Nudix Proteins Possessing Decappsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with a previous report, Nudt16 hydrolyzed the GpppRNA unmethylated capped RNA and generated GMP decapping product ( Fig. 1C; Ghosh et al 2004). Unexpectedly, Dcp2 could also hydrolyze GpppRNA and released GDP.…”
Section: Identification Of Mammalian Nudix Proteins Possessing Decappsupporting
confidence: 92%
“…Nudt16 was initially identified in Xenopus as a nucleolar decapping enzyme that specifically binds the U8 snoRNA (Tomasevic and Peculis 1999;Ghosh et al 2004). It was subsequently shown to be a cytoplasmic protein in mammalian cells and involved in mRNA decapping (Song et al 2010).…”
Section: Eukaryotic Mrnas Are Modified With Amentioning
confidence: 99%
“…The recent demonstrations that both Dcp2 and Nudt16 possess transcript-specific decapping properties (Ghosh et al 2004;Li et al 2008Li et al , 2009) prompted us to test whether various mRNA decay processes differentially utilized the two decapping enzymes and assessed their roles in nonsense-mediated decay (NMD), ARE-mediated decay, and noncoding RNA-mediated gene silencing. The effect of Dcp2 on the reduction of nonsense mRNA levels was assessed by transiently transfecting MEF cells with plasmids encoding either a normal b-globin transcript lacking a nonsense mutation (Norm) or its nonsense mutation-containing version (PTC39).…”
Section: Preferential Utilization Of Dcp2 In Nmdmentioning
confidence: 99%
“…The X29 protein was first identified in Xenopus as a nuclear decapping protein that specifically binds U8 snoRNA (Tomasevic and Peculis 1999;Ghosh et al 2004). However, we recently demonstrated that the mammalian homolog, Nudt16, is a cytoplasmic decapping enzyme and can regulate the stability of specific mRNA substrates (Song et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the nuclear decay of pre-mRNAs and nuclear-restricted mRNAs also seems to involve decapping of such transcripts (Kufel et al 2004). A nuclear protein with decapping activity, Nudt16/X29, is conserved in several organisms (Taylor and Peculis 2008) and has the ability to cleave both m 7 -monomethyl and m 2,2,7 -trimethyl caps (characteristic of snRNAs and snoRNAs) of RNAs in vitro (Ghosh et al 2004), implying that decapping may be a required step in the decay of several different RNA substrates in the nucleus.…”
Section: Introductionmentioning
confidence: 99%